Prediction of amount solid waste in Morogoro Municipal council - Malata, Ritha Isdory (Mzumbe Unversity, 2024)
A research report submitted in partial fulfillment of the requirements for award of Master of Science project planning and management (MSc. PPM) of Mzumbe University